Optimizing Agricultural Production Through the Internet of Things: Innovative Solutions to Reduce Food Loss and Waste - Ardhy, Muhammad Maliki; Sinaga, Hanif Zaidan; Pratama, Muhammad Akmal Putra; Maulana, Akhmad Dzulfiqar; Abdullah, Arsyad (inovator, 2024)
Significant food loss and waste along agricultural supply chains is a global challenge that threatens food security and environmental sustainability. This research aims to explore the potential of Internet of Things (IoT) technology as an innovative solution to overcome these problems. Through an interdisciplinary approach that combines agriculture, information technology and sustainability, this research develops an integrated Internet of Things (IoT) system that can efficiently monitor, analyze and manage the entire agricultural supply chain process. The proposed Internet of Things (IoT) solution includes a wireless sensor network for real-time monitoring of environmental conditions, crop growth, and activity on farmland, as well as a cloud-based analytics platform to process data and provide optimal recommendations. In addition, this system also allows food product traceability and information transparency along the supply chain. Respondents who are agricultural managers have a positive perception of the use of Internet of Things (IoT) technology in their agricultural activities. The research instrument (questionnaire) used was also proven to be valid and reliable in measuring related variables. Thus, this research concludes that the application of Internet of Things (IoT) technology in smart farming has great potential to optimize input use, increase crop productivity, and significantly reduce food loss and waste through better monitoring and control along the agricultural supply chain.